Successful treatment of recalcitrant follicular lichen planus (lichen planopilaris) with the topical JAK 1/2 inhibitor ruxolitinib - Tanja Fetter; Dagmar Wilsmann‐Theis; Luka deVos‐Hillebrand; Natalija Novak; Joerg Wenzel (JEADV Clinical Practice)
Abstract We report the successful treatment of a patient with refractory follicular lichen planus (LP) with topical ruxolitinib, a Janus kinase (JAK) 1/2 inhibitor, which resulted in significant improvement of lesional skin within 1 month of daily use.